Predictors of Middle School Students' Interest in Participating in an Incentive-Based Tobacco Prevention and Cessation Program in Connecticut - Morean, Meghan E. (Hindawi Publishing Corporation, 2014)
Behavioral incentives have been used to encourage smoking cessation in older adolescents, but the acceptability of incentives to promote a smoke-free lifestyle in younger adolescents is unknown. To inform the development of novel, effective, school-based interventions for youth, we assessed middle school students' interest in participating in an incentive-based tobacco abstinence program. We surveyed 988 students (grades 6–8) attending three Connecticut middle schools to determine whether interest in program participation varied as a function of (1) intrapersonal factors (i.e., demographic characteristics (sex, age, race), smoking history, and trait impulsivity) and/or (2) aspects of program design (i.e., prize type, value, and reward frequency). Primary analyses were conducted using multiple regression. A majority of students (61.8%) reported interest in program participation. Interest did not vary by gender, smoking risk status, or offering cash prizes. However, younger students, non-Caucasian students, behaviorally impulsive students, and students with higher levels of self-regulation were more likely to report interest. Inexpensive awards (e.g., video games) offered monthly motivated program interest. In sum, middle school students reported high levels of interest in an incentive-based program to encourage a tobacco-free lifestyle. These formative data can inform the design of effective, incentive-based smoking cessation and prevention programs in middle schools.